Immunotherapy and tyrosine kinase inhibitors in chordoma: a real-world data study from a European Reference Network on Rare Adult Solid Cancers member center - Balsa, Mario; Torrent, Francesc; Pérez, Diana; Ruiz, Alejandro; Viñals, Joan Maria; Pablos, Oscar; Fontalva, Maria; Portabella, Federico; Lozano, Alicia; González-Viguera, Javier; Narváez, Jose Antonio; Hernández, Javier; et al. (Frontiers in Oncology, 2026)
IntroductionChordoma is a rare malignant tumor originating in the notochord characterized by slow progression but frequent recurrences. Systemic treatment for this condition is not well defined. This study aimed to describe real-world clinical practice patterns of systemic therapy and its outcomes in patients with advanced chordoma treated at a sarcoma referral center member of the European Reference Network on Rare Adult Solid Cancers (EURACAN).MethodsConsecutive adult patients with histologically confirmed chordoma, diagnosed between 2005 and 2024, who received tyrosine kinase inhibitors (TKI) or immune checkpoint inhibitors (ICI), were retrospectively reviewed. Demographic, clinicopathological, and treatment data were collected from institutional databases. Responses were radiologically assessed according to RECIST criteria by sarcoma radiologists as part of routine clinical care. Data were collected up to December 31, 2024.ResultsA total of 13 patients (median age 62 years) were identified. All had undergone surgery, and more than half received adjuvant radiation therapy. Most patients (n=10, 76.9%) received systemic therapy with imatinib as first-line treatment, while a minority (n=2, 15.4%) received ICIs as first-line therapy. Several patients received multiple lines of treatment, including sequential exposure to TKI and ICI. Objective responses were observed in 2 of 5 patients in the TKI-only subgroup (40.0%) and 4 of 8 patients in the ICI-exposed subgroup (50.0%), all of which were partial responses, with prolonged disease stabilization being the a common outcome. The median progression-free survival (PFS) for the entire cohort was 12.3 months, and the median overall survival (OS) was 149.8 months. The median PFS and median OS in the TKI-only subgroup were 7.4 and 113.5 months, respectively, whereas they were 12.7 and 151.6 months in the ICI-exposed subgroup, respectively. Subgroup results are descriptive, exploratory, and hypothesis-generating due to the small sample size.ConclusionOur results indicate that systemic therapy can provide durable disease control in selected patients with chordoma. TKI are commonly used and may provide good responses while ICIs show potential activity in selected patients but await confirmation in robust clinical trials. These real-world data reinforce the need for prospective, multicenter studies to optimize treatment sequencing and patient selection in this rare malignancy.